2018
DOI: 10.3390/nano8070558
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Laser-Based Modification of PDMS to Electrically Conductive Silicon Carbide

Abstract: In this paper, we experimentally demonstrate femtosecond laser direct writing of conductive structures on the surface of native polydimethylsiloxane (PDMS). Irradiation of femtosecond laser pulses modified the PDMS to black structures, which exhibit electrical conductivity. Fourier-transform infrared (FTIR) and X-ray diffraction (XRD) results show that the black structures were composed of β-silicon carbide (β-SiC), which can be attributed to the pyrolysis of the PDMS. The electrical conductivity was exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 25 publications
(29 reference statements)
2
16
0
Order By: Relevance
“…6(d), lattice fringes with a spacing of approximately 0.25 nm were observed. This spacing corresponds to the (111) plane of b-SiC and, consistent with the previous reports by Nakajima et al, 17 the formation of crystalline SiC is indicated. Additionally, since the direction of the fringes is consistent throughout the observed monocrystalline structure, the observed structure is presumed to be a single nanoparticle of SiC.…”
Section: Tem Observation Of the Fabricated Structuresupporting
confidence: 91%
See 1 more Smart Citation
“…6(d), lattice fringes with a spacing of approximately 0.25 nm were observed. This spacing corresponds to the (111) plane of b-SiC and, consistent with the previous reports by Nakajima et al, 17 the formation of crystalline SiC is indicated. Additionally, since the direction of the fringes is consistent throughout the observed monocrystalline structure, the observed structure is presumed to be a single nanoparticle of SiC.…”
Section: Tem Observation Of the Fabricated Structuresupporting
confidence: 91%
“…A laser power of 150 mW and scanning speed of 2 mm s À1 were selected for the fabrication of the line structure, since SiC with high crystallinity and high electrical conductivity was reported previously using these fabrication parameters. 17 SEM images of the surface show a signicant increase in surface roughness with laser irradiation ( Fig. 4(a)).…”
Section: Resultsmentioning
confidence: 99%
“…Such trenches are observed for all the structures previously fabricated by the laser modification of PDMS, regardless of the wavelength, pulse duration, power, and scanning speed during fabrication. [ 16–18 ] For the structure fabricated with a defocus distance of 50 μm, a similar but thinner trench can be observed (Figure 2b). In contrast, for the structures fabricated with defocus distances of 100 and 150 μm, no trenches are observed (Figure 2c,d).…”
Section: Resultsmentioning
confidence: 69%
“…[15] The laser modification of PDMS into electrically conductive structures has been recently demonstrated. [16][17][18] Using PDMS as a precursor, the realization of elastic PDMS-based flexible devices, without previously required transferring/coating or filler loading, can be expected. [19][20][21][22] However, the conductivities of the structures fabricated using PDMS as the precursor are significantly lower than those fabricated using other polymers, possibly due to the aliphatic structure of PDMS, which cannot be easily graphitized.…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with the lower abundance of Si atoms in the starting material due to the presence of 40% TEG. The presence of the nanoparticles is not surprising: laser‐induced synthesis of SiC nanoparticles from PDMS substrates has already been reported in the literature [ 16,18 ] and they are expected to play an important role in the electrical characteristics of the samples, lowering the conductivity of the material. Regarding the graphenized area, for both samples high‐resolution TEM images clearly show the presence of a complex structure of randomly oriented few‐layer graphene domains, characterized by the ≈3.4 Å d ‐spacing of the (002) family of planes in graphite.…”
Section: Resultsmentioning
confidence: 99%